2021
DOI: 10.1177/00420980211023206
|View full text |Cite
|
Sign up to set email alerts
|

Land use disadvantages in Germany: A matter of ethnic income inequalities?

Abstract: Environmental hazards affect people from different income groups and migration backgrounds on different levels. The research on environmental inequalities and environmental justice has proposed several theories to explain such inequities; still, it remains unclear which of these theories applies to the German societal context. This research investigates whether individual-level income differences between Germans and migrants account for objectively measured exposure to the environmental goods and bads of land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Market disadvantages theory (MDT), otherwise called the iron cage perspective, is traced to the pioneering works of Weber (1930) and Light (1979), who both affirmed that racial discrimination in employment engenders employment disadvantages or exclusion from economic activities. The MDT explains the degree of immigrant integration into the labor market in the host countries when measured in terms of immigrant composition, the number of employees, and occupational status in the host countries (Jünger 2021). The MDT is beneficial for explaining transitional entrepreneurs, such as immigrants, ethnic groups, and minorities, who take up entrepreneurship as an economic survival strategy in foreign countries (Light 1979;Smith-Hunter and Boyd 2004;Chrysostome 2010).…”
Section: Theoretical Review Of Entrepreneurship Venturingmentioning
confidence: 99%
See 1 more Smart Citation
“…Market disadvantages theory (MDT), otherwise called the iron cage perspective, is traced to the pioneering works of Weber (1930) and Light (1979), who both affirmed that racial discrimination in employment engenders employment disadvantages or exclusion from economic activities. The MDT explains the degree of immigrant integration into the labor market in the host countries when measured in terms of immigrant composition, the number of employees, and occupational status in the host countries (Jünger 2021). The MDT is beneficial for explaining transitional entrepreneurs, such as immigrants, ethnic groups, and minorities, who take up entrepreneurship as an economic survival strategy in foreign countries (Light 1979;Smith-Hunter and Boyd 2004;Chrysostome 2010).…”
Section: Theoretical Review Of Entrepreneurship Venturingmentioning
confidence: 99%
“…Level 1 uncertainty presents a clear future with likelihoods, possibilities, and probabilities of success for ethnic, immigrant, and women entrepreneurs in their operating environment, usually in developed countries such as the UK, the US, Canada, and Australia, where there are new market opportunities and strong support for transitional entrepreneurship. Furthermore, Level 2 uncertainty presents several alternate paths and trajectories of ethnic, immigrant, and women entrepreneurs in Western European countries that are particularly successful in integrating ethnic minorities and immigrants (Jünger 2021). Some of the reported types of uncertainty facing transitional entrepreneurs in Britain, Scotland, and by extension other Western countries that largely influence the success or failure of transitional entrepreneurship include racial discrimination, drop-in paid employment, insufficient economic reward in self-employment, language difficulties, business venturing risk, restrictive immigration policy, low participation in postcompulsory education, the level of entrepreneurial ambitions, demographic change, lower returns in retail and small businesses, rising competition in business venturing, and globalization waves (Jones and Ram 2003;Blanchflower 2004;Deakins et al 2007;Siqueira 2007;Clark and Drinkwater 2010;Li et al 2003).…”
Section: Total 17mentioning
confidence: 99%
“…Examples of spatial topics in the social sciences include labour market dynamics (Martén et al 2019, Nisic 2017, Zoch 2021, processes of residential segregation (Roberto 2018, Tóth et al 2021) and gentrification (Fransham 2020, Zapatka & Beck 2021, the spatial distribution of environmental goods or bads (Boillat et al 2022, Jünger 2022, Rüttenauer 2018, the consequences of extreme weather events (Ogunbode et al 2019, Hoffmann et al 2022, Rüttenauer 2023 or the access to infrastructural conditions (Moreno-Monroy et al 2018, Liao et al 2020, Wiedner et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…The expo sure level to envi ron men tal pol lu tion is not equally dis trib uted across households. Research has shown that eth nic and racial minor i ties in the United States as well as in Europe are dis pro por tion ately exposed to envi ron men tal harms (e.g., Ard 2015;Glatter-Götz et al 2019;Jünger 2021;Mohai and Saha 2015a;Pasetto et al 2019;Pastor et al 2005;Rüttenauer 2018Rüttenauer , 2019a. Similarly, eco nom i cally dis ad vantaged house holds tend to live in areas with higher lev els of envi ron men tal pol lu tion (e.g., Ash and Fetter 2004;Downey and Hawkins 2008;Raddatz and Mennis 2013;Wolverton 2009).…”
Section: Introductionmentioning
confidence: 99%